Fuzzy-PID Control for Balancing a Two-Wheeled Inverted Pendulum Robot - Fahmizal; Afrizal Mayub; Lintang Fathia Rafanah; Smail Latifa (Peneliti Teknologi Teknik Indonesia, 2026)
A two-wheeled inverted pendulum robot (TWIPR) requires continuous control action because its upright position is inherently unstable and highly sensitive to disturbances. This research proposes the use of a fuzzy-PID controller to keep the TWIPR balanced. Although PID has several advantages, its performance can degrade when the system is subjected to changing conditions. To address this, fuzzy logic is applied to enhance the adaptive capabilities of the PID controller. The fuzzy system dynamically generates PID parameters based on predetermined fuzzy rules, effectively maintaining system stability. The fuzzy membership functions used, namely MF3, MF5, and MF7, were compared through no-load and loaded tests. In the no-load test, the fuzzy-PID with MF7 reduced rise time, settling time, overshoot, peak value, and peak time by 1.229%, 0.673%, 86.703%, 7.232%, and 2.952%, respectively, compared with those of the conventional PID. However, the MF3 configuration only excels in overshoot and peak time, while the MF5 configuration only shows improvements in settling time, overshoot, and peak value. Further testing results show that Fuzzy-PID with MF7 provides the most stable performance under load conditions.